PERSEPSI PENGELOLA VILA DI KUTA UTARA TERHADAP PENGGUNAAN ONLINE TRAVEL AGENTS UNTUK PROMOSI DAN PENJUALAN - Astuti, Luh Sri (Jurnal Master Pariwisata (JUMPA); Volume 02, Nomor 01, Juli 2015DO - 10.24843/JUMPA.2015.v02.i01.p06)
There has been a growing tendency for villa and accommodationbusiness worldwide to use online travel agents (OTA) to promoteand sell their rooms. This research discusses the advantagesand disadvantages of the promotion and sales through OTA forvilla business in North Kuta area and analyses motivation andperception of the villa management in using OTA. The objectof the research is the villa manager, supervisors and staff whohandle the villa promotion and sales of their accommodationbusiness. Villas were chosen based on cluster proportionaland the informants were chosen based on purposive samplingtechnique. The result shows that the disadvantages in usingOTA as promotion and sales tool are rising occupancy, directpayment, and as a tool in making villa well known worldwide.The disadvantages are decrease net sales, over booking,negative comments could downgrade the villa’s rank, and OTAmake villa’s website got limited traffic. The motivation of villamanagements in using OTA is highly motivated. The dominantfactor of the perception included factors in self-perception ofthe target, factor in the self-perception., and factors perceptionof situation. This research suggests to the villa management torecruit special personnel for handling OTA as well as to manageown websites to increase the net sales.
Keywords: perception, villa management, online travel agents, North Kuta area.